Impact of Deficit Irrigation on Bell Pepper (Capsicum annuum var. Grossum) Cultivation - Ridwan, Ridwan; Nugroho, Annas Setia Bekti; Amien, Elhamida Rezkia; Amin, M.; Asmara, Sandi (Jurnal Agricultural Biosystem Engineering, 2024)
The purpose of this study is to determine the effect of deficit irrigation application on the growth of bell pepper plants and to assess the efficiency of irrigation water application for bell pepper plants. The design used in this research is a Completely Randomized Design with 4 levels of deficit irrigation treatments and six replications. The procedures involved in this study include analysis of soil moisture to determine field capacity and permanent wilting point, treatment conditioning, planting, plant maintenance, observations, and finally, harvesting. The data obtained were tested for homogeneity of variances using the F-test, and if there were differences among treatments, further analysis was conducted using the Least Significant Difference test at the 5% level. The results of the data analysis are presented in tables, graphs, and diagrams. Deficit irrigation treatments significantly affected the plant height and leaf number parameters. The plant response to irrigation was limited under deficit irrigation based on total fruit weight, where bell pepper plants produced the best fruit under the 80% deficit irrigation treatment, with an average total fruit weight of 242.17 grams. Meanwhile, in the ID4 treatment, the plant results were less favorable due to stress. The response of the results to water (Ky) indicates that the Ky value (Ky <1) for bell pepper plants in the ID2, ID3, and ID4 treatments shows values less than 1, meaning that these treatments are tolerant to water stress. Keywords: Bell Pepper, Deficit irrigation, Irrigation, Yield response